ISU MUKTAHIR SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DI PERUSAHAAN - Syaidil Amri; Susilawati Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
Occupational Safety and Health (K3) is the most important part in managing risk management by a company or organization in safety. in safety includes 2 parts, namely safety risks and health risks. Occupational health refers to conditions that allow you to be free from physical disturbances, bruises, pain, and emotions caused by the work environment. K3 management system is a system that exists within the company as a whole in order to control risks related to work activities in order to create a comfortable, safe, efficient and productive work environment. The type of data used is secondary data. Which is where data collection is done by literature study, then the data is analyzed, processed, and concluded.